2018
DOI: 10.1002/crat.201800042
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of GaN(1−x)Asx, Zinc‐Blende, or Wurtzite GaN Depending on GaAs Nitridation Temperature in a CVD System

Abstract: The study of GaN morphology and structure modification due to the variation of the nitridation temperature are reported. GaN is obtained by nitridation of GaAs (1 1 1) using the flow of a mixture of hydrogen and ammonia into a horizontal CVD system. The experiments are carried out at atmospheric pressures of 800, 900, and 1000°C for 1 h. XRD results together with the pole figure indicate that GaN (1-x) As x is obtained at 800°C, that zinc-blende GaN structure is obtained at 900°C, and that wurtzite GaN structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The hydrophilic and hydrophobic properties of porous GaN epitaxial layer materials are discussed and explained using the Cassie-Baxter model. FS Ramí rez-Gonzá lez [13] reported that GaN films were prepared by a CVD system using GaAs (1 1 1) and ammonia as the reaction source and hydrogen as the carrier gas. In their report, the photoluminescence emission peaks changed from 420 nm to 384 nm and 372 nm as the temperature changed from 800 °C to 900 °C and 1000 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophilic and hydrophobic properties of porous GaN epitaxial layer materials are discussed and explained using the Cassie-Baxter model. FS Ramí rez-Gonzá lez [13] reported that GaN films were prepared by a CVD system using GaAs (1 1 1) and ammonia as the reaction source and hydrogen as the carrier gas. In their report, the photoluminescence emission peaks changed from 420 nm to 384 nm and 372 nm as the temperature changed from 800 °C to 900 °C and 1000 °C.…”
Section: Introductionmentioning
confidence: 99%